Effects of Venous Insufficiency in Patients Undergoing Primary Total Knee Arthroplasty: An Analysis of 1.2 Million Patients - Summers, Spencer; Yakkanti, Ramakanth; Ocksrider, Justin; Haziza, Sagie; Mannino, Angelo; Roche, Martin; Hernandez, Victor H. (The Journal of Knee Surgery, 2021)
Chronic venous insufficiency (CVI) is extraordinarily prevalent in our aging population with over 30 million people in the United States suffering from the disease. There is a paucity of data analyzing the effects of CVI on outcomes following total knee arthroplasty (TKA). The purpose of this study was to utilize a nationwide administrative claims database to determine whether patients with CVI undergoing TKA have higher rates of: (1) in-hospital lengths of stay (LOS); (2) readmission rates; (3) medical complications; (4) implant-related complications; and (5) costs of care compared to controls. Using a nationwide database, we matched patients with CVI undergoing TKA to controls without CVI undergoing TKA in a 1:5 ratio by age, sex, and medical comorbidities associated with CVI. Primary outcomes analyzed within the study included LOS, 90-day readmission rates, 90-day medical complications, 2-year implant-related complications, in addition to 90-day total global episode of care costs. The query yielded 1,265,534 patients with (n = 210,926) and without (n = 1,054,608) CVI undergoing primary TKA. Patients with CVI had significantly longer LOS (4 vs. 3 days, p < 0.0001), higher 90-day readmission rates (20.96 vs. 15.34%; odds ratio [OR]: 1.46, 95% confidence interval [CI]: 1.44–1.48, p < 0.0001), and higher odds of medical complications (2.27 vs. 1.30%; OR: 1.76, 95% CI: 1.70–1.83, p < 0.0001) compared to matched controls. Patients with CVI also had higher odds of periprosthetic joint infections (2.23 vs. 1.03%; OR: 2.18, p < 0.0001) and implant-related complications in general (4.27 vs. 2.17%; OR: 2.01, 95% CI: 1.96–2.06, p < 0.0001). Additionally, patients with CVI had higher total global 90-day episode of care costs ($15,583.07 vs. $14,286.95, p < 0.0001). Patients with CVI undergoing TKA have increased LOS, higher odds of medical and implant complications, and increased costs of care compared to those without CVI. The study can be utilized by orthopaedic surgeons to counsel patients on the potential complications following this procedure. This is a level III, retrospective cohort study.
Keywords: venous insufficiency; total knee arthroplasty; Medicare; complications; costs